Dose measurements nearby low energy electronic brachytherapy sources using radiochromic film. (August 2019) - Devic, Slobodan; Liang, LiHeng; Tomic, Nada; Bekerat, Hamed; Morcos, Marc; Popovic, Marija; Watson, Peter; Aldelaijan, Saad; Seuntjens, Jan
Highlights: Dose measurements around 50 kVp electronic brachytherapy source. Radiochromic film linear response function. Impact of beam hardening effect around 50 kVp sources. Abstract: Purpose: We investigate the effect of the GafChromic™ film EBT3 model absorbed dose energy response when used for dose measurements around low-energy photon sources. Monte Carlo based correction procedure in synergy with appropriate calibration curves was shown to provide more accurate absorbed dose (either relative or absolute). An assessment was made of possible dose errors that might be encountered if such energy dependent response is ignored. Methods: We measured PDDs in water from a Xoft 50 kVp source using EBT3 film, and compared to PDD measurements acquired with a PTW-TN34013 parallel-plate ionization chamber. For the x-ray source, we simulated spectra using the EGSnrc (BEAMnrc) Monte Carlo code, and calculated Half Value Layer (HVL) at different distances from the source in water. Measurement strips of EBT3 film were positioned at distances of 2–6 cm from the Xoft source in a water phantom using a custom-made holder and irradiated simultaneously. Results: Our results show that film calibration curves obtained at beam qualities near the effective energy of the Xoft 50 kVp source in water lead to variation in absorbed dose energy dependence of the response of around 5%. However, if the calibration curve was established in an MV beam quality, the error in absorbed dose could be as large as 20%. Conclusion: Accurate dose measurements using radiochromic films at low photon energies require that the radiochromic film dosimetry system be calibrated at appropriate corresponding low energies, as large absorbed dose errors are expected when film calibration is performed in MV beam qualities.